Case Study of Effectiveness Evaluation of Staff Training Courses in Refah Bank - Yousefian, E.; Chitsaz, A.; Karimpour, B. (Engineering, Technology & Applied Science Research, 2017)
One of the newest and most well-known train patterns for evaluating the effectiveness of in-service staffs training is Kircpatrick model. In this paper, the effectiveness of staff training courses of Refah-bank is evaluated. A questionnaire consisted of five components which include: reaction, learning, of behavior, the results and the innovation in role of confounding factors is handed out. The survey results show that three factors (reactions, behavior and innovation) have a significant effect on the teachings effectiveness according to Kircpatrick model. And that two factors (learning and results of the courses) have not a significant effect.